1997
DOI: 10.1080/01140671.1997.9513992
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan coating for inhibition of sclerotinia rot of carrots

Abstract: In in vitro tests, chitosan at 1, 2, and 4% (w/v) significantly reduced the growth of Sclerotinia sclerotiorum on potato dextrose agar plates. The effect of chitosan coating on sclerotinia rot of carrots (Daucus carota L.) held at 22°C was also investigated. Carrot roots were coated with chitosan solutions (2 or 4%) and inoculated with mycelial plugs of S. sclerotiorum culture. After 5 days of storage, chitosan at both rates reduced significantly the incidence of rot (from 88 to c. 28%) and also the lesion siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(38 citation statements)
references
References 12 publications
3
31
0
4
Order By: Relevance
“…radicislycopersici, and S. sclerotiorum treated with chitosan. These studies showed excessive mycelial branching, abnormal shapes, swelling, and hyphae size reduction (Benhamou 1992;Cheah et al 1997). Large vesicles or empty cells devoid of cytoplasm in the mycelium of B. cinerea, treated with chitosan, were observed by Ait Barka et al (2004).…”
Section: Resultsmentioning
confidence: 99%
“…radicislycopersici, and S. sclerotiorum treated with chitosan. These studies showed excessive mycelial branching, abnormal shapes, swelling, and hyphae size reduction (Benhamou 1992;Cheah et al 1997). Large vesicles or empty cells devoid of cytoplasm in the mycelium of B. cinerea, treated with chitosan, were observed by Ait Barka et al (2004).…”
Section: Resultsmentioning
confidence: 99%
“…EI Ghaouth reported that chitosan could inhibit the growth of Alternaria alternata, Botrytis cinerea, Colletrotichum gloeosporioides and Rhizopus stolonifer (EI Ghaouth et al, 1992). Cheah reported the inhibitory effect of chitosan against Sclerotinia sclerotiorum, and the inhibitory index was affected by the concentration of chitosan (Cheah et al, 1997). At the same time, the growth of fungi such as F. oxysporum, R. stolonifer, Penicillium digitatum and C. gloeosporioides can be completely inhibited by chitosan at the concentration of 3% (Bautista-Baños et al, 2003;BautistaBaños et al, 2004;Bautista-Baños et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…키틴은 토양 미생물상을 변화시켜 토양 병원균을 억 제하고 (Cretoiu et al, 2014), 키틴분해효소를 분비하는 미 생물을 촉진하여 식물기생성 선충을 감소시키는 효과도 있 다 (Sarathchandra et al, 1996). 키토산도 식물병원성 세 균과 곰팡이를 억제하고 (Cheah et al, 1997;Rabea and Steurbaut, 2010), 식물기생성 선충의 피해를 감소시킨다 (Khalil and Badawi, 2012). 또한, 키토산을 식물에 처리하 면 병원균을 억제하는 물질의 생성을 유도하는 효과가 있다 (Walker et al, 2003).…”
Section: 키틴과 키토산은 토양생물에게 먹이원이 되며 이차적으 로는 분해된 물질이 식물의 양분으로 이용되기 때문에 농unclassified